Clinico-Epidemiological Profile of Extra-pulmonary Tuberculosis in Central India - Arun Kumar Shrivastava; Swagata Brahmachari; Prashant Pathak; Ratan Kumar; Tarun Sainia; Umesh Patel; Amar Mandil (International Journal of Medical Research and Review, 2015)
Introduction: Tuberculosis (TB) remains a major global health issue. India being highest TB burden country needs concern. It was found that the percentage of patients with EPTB was more in tertiary care centres of India, ranging from 30% to 53%. The primary objective of this study was to describe the basic demographic, clinical characteristics and risk factors of Extrapulmonary Tuberculosis in patients, registered at DOTS centre of tertiary care teaching hospital.Materials and Methods: This is a retrospective, record-based study of patients of EPTB, at the LN Medical College and Hospital, Bhopal, from 1st January 2012 to 30th June 2014.Results: Among 491 cases registered for treatment of all forms of tuberculosis, 361(73.53%) had PTB and 130 (26.47%) had EPTB. The ratio of percentage EPTB: PTB is 1:3.6. Commonest type of EPTB was found in cases of lymph nodes and lymphatic (30.76%), followed by TB in pleural cavity (23.03%). Among different age groups studied, the age group of 20-39 years had the highest proportion of EPTB both in males and females which is the economically productive population of society.Conclusion: The frequency of EPTB in this study was higher (26.47%) with the highest proportion in lymph node (30.76%). The burden of EPTB is more among the productive age group, moreover, being male, young adults and having associated diabetes mellitus were significant risk factors for patient being EPTB positive.